ПРОБЛЕМА ПРОФЕСІЙНОЇ ПІДГОТОВКИ ВИКЛАДАЧІВ ВИЩОЇ ШКОЛИ У ПЕДАГОГІЧНІЙ ТЕОРІ - Batechko, N (Continuing Professional Education: Theory and Practice, 2019)
The article deals with general problems of high school teachers’ training and solutions of such problems from positions of pedagogical theory. Attention is paid to a number of contradictions between the level of professional and pedagogical training of higher educational institutions teachers and between modern requirements of high school. The role of master-degree in the future teachers’ professional formation has been analyzed.